EFEKTIVITAS PENGGUNAAN SISTEM VISUAL HOTEL PROGRAM (VHP CLOUD) PADA PROSES TRANSAKSI HARIAN DI GRAND PERMATA HIJAU HOTEL SUKABUMI - Farhan Puadi; Kharisma, Kharisma (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the effectiveness of implementing a cloud-based Property Management System (PMS), specifically the Visual Hotel Program (VHP Cloud), in optimizing daily transaction processes at Grand Permata Hijau Hotel Sukabumi. Managing an operational capacity of 93 rooms, the hotel requires high accuracy and speed in its services. A descriptive qualitative method with a case study approach was utilized through observation, documentation review, and in-depth interviews with Front Office and Accounting staff. The results indicate that VHP Cloud effectively reduces check-in/check-out times from an average of 5–7 minutes to under 3 minutes, minimizes human error in logging, and integrates financial data in real-time. The primary constraints identified are the absolute dependence on internet network stability and the system adaptation period required for new staff. Management is advised to provide a redundant internet link to maintain seamless operations.